The structure and nutritiousness of diets for milk cows with the annual milk from productivity 6-9 thousand kilograms - Трончук, І. С.; Рак, Т. М.; Чижанська, Н. В. (Scientific Progress & Innovations, 2012)
The perspective physiologically and economically proved structure of diets for highly productive milk cows has been developed. The research carried out by authors has shown that at high daily milk productivity it is necessary to limit a dose of a corn silo to 25-30 kg per a head for a day, and to increase the concentrated forages by 46-54 % on nutritiousness with the aim of normal consumption of demanded quantity of forages in diets. Offers concerning the organisation of high-grade feeding of milk cows throughout a year that guarantees manufacture of highquality profitable milk are given. Intensification level: annual milk productivity 6000-9000 kg; expenses of forages on 1 kg of milk - 9-10 МJ of exchange energy.